2019
DOI: 10.1111/btp.12623
|View full text |Cite
|
Sign up to set email alerts
|

The spatial genetic structure of the White‐banded Tanager (Aves, Passeriformes) in fragmented Neotropical savannas suggests two evolutionarily significant units

Abstract: Understanding the genetic structure of a species is crucial for evolutionary biology research and species conservation. The objectives of this study were to investigate the genetic structure of Neothraupis fasciata in Brazilian savannas and to assess genetic differentiation of its disjunct population in the Amazonian savannas of the state of Amapá. Population genetic structure was assessed in relation to isolation by distance and landscape variables connected with habitat heterogeneity. The influences of facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…This is an unexpected result, given the low dispersal from the birth area reported for this species (around 300 meters; [37]). However, a previous study of the genetic structure of this tanager using microsatellite markers also found no effect of geographic distance under the genetic differentiation among these same sampled locations [39]. The isolation-by-distance pattern occurs when the migration-drift equilibrium is reached, but it can take a relatively long time [79].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…This is an unexpected result, given the low dispersal from the birth area reported for this species (around 300 meters; [37]). However, a previous study of the genetic structure of this tanager using microsatellite markers also found no effect of geographic distance under the genetic differentiation among these same sampled locations [39]. The isolation-by-distance pattern occurs when the migration-drift equilibrium is reached, but it can take a relatively long time [79].…”
Section: Discussionmentioning
confidence: 88%
“…A previous study using a set of microsatellite markers found moderate genetic structure in N . fasciata and the distribution of the genetic variability was not explained by the isolation-by-distance hypothesis, habitat heterogeneity or by the core-periphery effect [ 39 ]. Similarly, the intense biome fragmentation by anthropic activity has not contributed significantly to the current pattern of genetic structure found in this species [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous studies of differentiation in Neotropical birds from open areas have found evidence for Pleistocene climatic oscillations as a driver of intraspecific divergence (Lima-Rezende et al 2019b, Rocha et al 2020, Ritter et al 2021. For instance, the genetic differentiation of narrowbilled woodcreeper Lepidocolaptes angustirostris populations seems to have occurred in allopatry in stable areas that formed during Pleistocene climatic fluctuations (Rocha et al 2020).…”
Section: Genetic Structuring In E Cristatamentioning
confidence: 99%
“…Our objective was thus twofold: to determine if geographic patterns of genetic diversity in North American gray wolves are consistent with the CMH, and to assess how the predicted edge effect interacts with the island effect. To that end, we tested how population genetic diversity varies in relation to two indices of the edge effect—latitude (Castellanos‐Morales et al, 2014; De Kort et al, 2021; Jenkins et al, 2018; Rodríguez‐Rodríguez et al, 2015; Wultsch et al, 2016) and distance to the center of the species' range (Langin et al, 2017; Lima‐Rezende et al, 2019; Natesh et al, 2017; Trumbo et al, 2016)—and we evaluated how these relationships are modified by island habitation.…”
Section: Introductionmentioning
confidence: 99%